Indoor temperature control of the VCC-based refrigeration systems - Pan, Jian (2011)
This report documents the learning experiences and knowledge gained by the author during the Final Year Project on The Indoor Temperature Control of the VCC based refrigeration system. Vapor Compression Cycle (VCC) based refrigeration systems are the most common type of system found in refrigeration engineering. Its compact design, relatively high COP, reliability, safety and exibility make it a sensible choice for solving a refrigeration need.